The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/6647303
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Vibration Mitigation of a Cable-Stayed Bridge with Asymmetric Pounding Tuned Mass Damper

Abstract: In order to mitigate the seismic response of a cable-stayed bridge, a new type damping device named asymmetric pounding tuned mass damper (APTMD) is developed in this paper on the basis of the traditional symmetric pounding tuned mass damper. The novel APTMD has three parameters to be determined: the left-side gap, the right-side gap, and the frequency ratio. A numerical model of the APTMD damping system is established with consideration of both the computational efficiency and accuracy to enable the parametri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…A large amount of recent research on PTMD show that PTMD is highly effective at suppressing vibrations excited by harmonic excitations, vortices, earthquakes, or complex loads underwater (Jiang et al, 2017; Wang et al, 2018b). PTMD can suppress vibration of various structures including pipelines, (Song et al, 2016) cable-stayed bridges (Zhang et al, 2021b) and hollow structures (Duan et al, 2020; Zhao et al, 2020). In order to employ PTMD in large-scale structures, multi-PTMD (Northern MarianasTMD) was introduced (Lin et al, 2016; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of recent research on PTMD show that PTMD is highly effective at suppressing vibrations excited by harmonic excitations, vortices, earthquakes, or complex loads underwater (Jiang et al, 2017; Wang et al, 2018b). PTMD can suppress vibration of various structures including pipelines, (Song et al, 2016) cable-stayed bridges (Zhang et al, 2021b) and hollow structures (Duan et al, 2020; Zhao et al, 2020). In order to employ PTMD in large-scale structures, multi-PTMD (Northern MarianasTMD) was introduced (Lin et al, 2016; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Structural safety, within the seismic context, can be effectuated via appropriate vibration control and mitigation mechanisms [1,2,3]. The design of such devices is subjected to particular requirements with respect to the frequency content of the seismic input, which usually lies at the lower range, as well as to the aspect of dealing with protected systems of large mass [4].…”
Section: Introductionmentioning
confidence: 99%
“…In early studies of the mass block is located in the middle of the two delimiters but, parametric studies revealed that the gap is the key parameter that influences the vibration control effectiveness. After that, Zhang et al ( 2021) [8] proposed a new type damping device named asymmetric (PTMD) where two gaps of the APTMD can be set to different values. Results showed that, the APTMD is slightly better than the TMD and the PTMD.…”
Section: Introductionmentioning
confidence: 99%